(untitled) (Sebha University Conference Proceedings, 2024)
This study focused on the impact of adding silica fume (SF) and palm oil fuel ash (POFA) on the workability, compressive strength, and water absorption characteristics of high-strength mortar. The objective is to assess the impacts of different proportions of SF and POFA on mortar performance. Four types of mortar mixes were prepared: high strength mortar (HSM), high strength green mortar with 40% POFA (U40-HSGM), high strength green mortar with 5% SF (U40-SF5-HSGFM), and high strength green mortar with 15% SF (U40-SF15-HSGFM). The inclusion of 40% POFA improved workability, while adding SF slightly reduced it. The inclusion of silica fume improved compressive strength, with the highest obtained in U40-SF15-HSGFM. Further, water absorption increased with POFA substitution, but was decreased when SF was added instead. In summary, the combination of SF and POFA results in significant improvement in mechanical and durability characteristics in high-strength mortars.